Gender and climate change: Enabling people to reach their full potential in adapting agriculture to climate change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Women and men differ, that much is obvious. But many of the ways in which society treats men and women differently – such as division of labour, access to credit, decision-making power, ownership of land, opportunities for education and many others – are social constructs rather than biological facts. Those differences can change, and can change swiftly. The development community has embraced these ideas and explored ways to transform perceptions of gender roles, but more upstream research has been slow to move beyond seeing gender as the biological differences between men and women. For that reason the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) has made the need to understand and transform gender dynamics in relation to climate change one of its most important priorities. Given that women make up 40% of the agricultural labour force in low-income countries, and are largely responsible for household food security, transforming gender perceptions and norms is indeed critical for smallholder adaptation to climate change.